Peningkatan Pemahaman Akuntansi Dengan Menggunakan Software Zahir - Fidya Arie Pratama; Odi Nurdiawan (FKIP Unswagati, 2019)
STMIK IKMI have a student academic test when the students enter to STMIK IKMI, the result of the test is low. Low in this case will explains by categories the students get D 25% C 37% B 0% and all the students can not get A. The research uses kuasi eksperiments method with time series design that collaborate classroom action research. The result of research shows about pre test 1 until 4, the score of pre test 1 about 54,129, the score of pre test 2 about 55,548, the score of pre test 3 about 56,032, the score of pre test 4 about 56,097. Based on Kruskall Walls Test shows Asymp Sig score about 0,986 it means there is no significance differences between student perception for the first time and students understanding the materials. In second part of research the students learn accounting that use zahir accounting software for 6 meetings. In third part of research the students has a post test for 4 meetings and the results are the score of post test 1 62,6456, the results are the score of post test 2 70,065, the results are the score of post test 3 80,032, the results are the score of post test 4 86,742. The research analyze statistic test focus on pre test and post test by Kruskall Wall Test that shows Asymp Sig score about 0,000 it means there is a differences between the result of pre test and post test. This reality shows accounting learning by Zahir software gives the positive effect for improving (upgrading) student understanding about accounting.